Some LRS Bianchi type II string-dust cosmological models with time decaying vacuum energy Λ - Amirhashchi, Hassan; Dehzangi, Arash (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
A new class of LRS Bianchi type II string- dust cosmological models are obtained in which the expansion (ᶿ) in the model is assumed to be proportional to the shear (σ). To get the deterministic models of the universe we consider the case of Reddy string (ρ + λ = 0), where ρ and λ are the rest energy density and the tension density of the string cloud, respectively. It is shown that in all models the vacuum energy density Λ is a positive and decreasing function of time and it approaches a small positive value at late times which is supported by recent results from the observations of (SN Ia). The physical and geometrical behaviour of these models are discussed.